Findings and Utility of Chest Computed Tomography in Pediatric Tuberculosis - Moreno-Ballester, Victor; Aparici-Robles, Fernando; Marti-Bonmati, Luis; Escribano-Montaner, Amparo; Sanchez-Aparisi, Eugenio; Otero-Reigada, Carmen; Gomez-Pajares, Fernando (Journal of Pediatric Infectious Diseases, 2018)
The objectives of this study are to describe the radiologic abnormalities detected on chest computed tomography (CT) of children suffering from tuberculosis and identify in which asymptomatic children, with positive tuberculin skin test and normal chest radiography, CT has the highest diagnostic yield using a low radiation dose protocol. The most common finding on CT in cases of tuberculosis is lymphadenopathy with necrotic appearance. In asymptomatic children with positive tuberculin skin test and normal chest radiography, CT had higher diagnostic yield in children younger than 5 years, modifying the therapeutic approach in a high percentage of cases. Reduction kilovoltage (kV) and milliamperage (mA) protocols significantly decrease the radiation dose, keeping sufficient diagnostic quality.
Keywords: tuberculosis; computed tomography; radiation